Desain Revisi Penilaian Kurikulum 2013 Tahun 2017: Studi pada Mata Pelajaran Sejarah Kebudayaan Islam di Kabupaten Kutai Kartanegara - Santoso, Agus; Achmad, Andi (SYAMIL, 2018)
The low tendency to understand the implementation of the Curriculum 2013 assessment activities is one of the problems in Madrasas. The teacher as one of the actors in the madrasa becomes spearheads the success of learning. Related to the context of the assessment in the Curriculum 2013 at this time must be carried out systematically including the assessment of attitudes, knowledge and skills. The purpose of this study was to determine the desain of the revised assessment curriculum 2013 in 2017. This type of research is library research with data collection techniques using “panduan penilaian oleh guru dan satuan pendidikan SMP/MTs Revisi 2017” linked to the structure of the curriculum, syllabus History of Islamic Culture and education calendar of Tenggarong City Kutai Kartanegara District Learning Year 2017 / 2018 for SMP / MTs. The results of the study that the desain of the revised curriculum assessment 2013 in 2017 related to the History of Islamic Culture in the Islamic Education in Tenggarong City, Kutai Kartanegara Regency, are tied to 4 main keys, namely, the structure of the curriculum, syllabus, educational calendar and time distribution analysis. Spiritual attitude assessment desain uses observation techniques in the classroom and questionnaires outside the classroom. Whereas social attitude assessment uses observation techniques in the classroom, student self-assessment questionnaires and between students outside the classroom. While the knowledge assessment desain uses structured assignment techniques, written tests and oral tests. The desain of knowledge assessment uses performance techniques, projects and products and is archived in the form of portfolios. The final results of the assessment are in the form of leggers which consist of collated judgments in the form of report cards and can be evaluated through student absorption.